(untitled) (UNED Research Journal, 2018)
Water deficit affects can have negative effects on grain formation. I investigated the relationships between the characters of durum wheat (Triticum durum) and yield under drought stress and identified the most effective components of yield. I used 49 durum wheat genotypes (43 exotic and 6 local lines), in a lattice design (7×7) replicated twice, during tillering, stem elongation, anthesis and grain filling. There were positive correlations among harvest index (r=0,849), plant height (r=0,695), tillering (r=0,689), peduncle length (r=0,466) and grain yield. The number of seeds per spike (0,432), spike length (0,410) and 1 000 seed weight (0,385) had the highest direct effect on yield.